Cytotoxic effects of gold(i) complexes against colon, cervical and osteo carcinoma cell lines: a mechanistic approach. (29th August 2019) - Sulaiman, Adam A. A.; Kalia, Namarta; Bhatia, Gaurav; Kaur, Manpreet; Fettouhi, Mohammed; Altaf, Muhammad; Baig, Nadeem; Kawde, Abdel-Nasser; Isab, Anvarhusein A.
Abstract : Water-soluble gold(i ) complexes, [Au(Ipr)(L)]PF6 where L = thiourea (Tu)1 and N, N ′-dimethylthiourea (Me2 Tu)2, were synthesized from the parent 1, 3-bis(2, 6-di-isopropylphenyl)imidazol-2-ylidenechloridogold(i ) [(Ipr)AuCl] (0 ). Abstract : Water-soluble gold(i ) complexes, [Au(Ipr)(L)]PF6 where L = thiourea (Tu)1 and N, N ′-dimethylthiourea (Me2 Tu)2, were synthesized from the parent 1, 3-bis(2, 6-di-isopropylphenyl)imidazol-2-ylidenechloridogold(i ) [(Ipr)AuCl] (0 ). The complexes (0–2 ) were fully characterized using elemental analysis (EA), FT-IR, 1 H and 13 C NMR spectroscopy. Single crystal X-ray diffraction analysis shows that both complexes have a near linear geometry. We investigated the in vitro cytotoxic activity of the complexes and cisplatin using an MTT assay against human osteosarcoma (MG-63), colon adenocarcinoma (HCT15), and cervical cancer (HeLa) cell lines. The IC50 values showed that the complexes1 and2 exhibit cytotoxicity higher than that of cisplatin against all cancer cell lines. The complex2 exhibited cytotoxicity less than that of cisplatin against HeLa. The interaction of the complexes with amino acids was tested electrochemically in a phosphate buffer aqueous solution using cyclic voltammetry. Complex1 interacted more withl -tryptophan than complex2 . The interaction of both complexes withl -tryptophan resulted in the reduction in peak height and peak current ofl -tryptophan. Studying the expression levels of caspase-3 and caspase-9 genes provided insight into the cell death mechanism. The treatment of the HCT-15 and HeLa cells with complex1 resulted in the induction of apoptosis and a significant up-regulation in the expression of both caspase-3 and 9. No significant deviation was noted in the expression of the MG-63 cells treated with complex1 .